Bioactive Content of Rose Hips of Different Wildly Grown Rosa dumalis Genotypes - Sevket ALP; Sezai ERCISLI; Tunde JURIKOVA; Ozlem CAKIR; Sadiye GOZLEKCI (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2016)
A rose hip is the fruit of a rose plant and mostly belongs to Rosa canina and Rosa dumalis. These species are genuine found as wild in natural conditions, while in some countries are cultivated for their hips that are picked and used in a wide variety of preparations. Because they contain a variety of antioxidants, carotenoids, flavonoids, polyphenols, leucoanthocyanins and catechins, rose hips are considered to be a good cancer preventative. The Rosa genus has been the focus of many recent studies due to its potential benefic effects on treatment and prevention of several diseases. However, there are few in vitro studies concerning its composition and antioxidant capacity. The aim of the present study was to determine bioactive content, including ascorbic acid, total phenolics, total flavonoids, total carotenoids and antioxidant activity of Rosa dumalis genotypes growing wild in Erzurum province located eastern Anatolia. The results revealed that fruits of Rosa dumalis different genotypes were rich rich in terms of vitamin C, which ranged from 402 to 511 mg/100 g fresh weight base. The total phenolic content varied from 297 to 403 mg/100 g fresh weight. The genotype ‘E-09’ had the highest total flavonoids content (229 mg quercetin equivalent/100 g fresh weight) and the lowest value was attributed to genotype ‘E-04’ with 143 mg/ quercetin equivalent/100 g fresh weight. The antioxidant activity of the genotypes was between 12.9-28.6 μg Trolox/ml samples. The results revealed that there was enough diversity among Rosa dumalis genotypes for bioactive content and promising genotypes, with high bioactive content, were determined, which can become study material for future breeding activities.